Improving Completion Rates for Client Intake Forms through Audio Computer‐Assisted Self‐Interview (ACASI): Results from a Pilot Study with the Avon Breast Health Outreach Program. Issue 6 (23rd August 2013) - Hallum‐Montes, Rachel; Senter, Lindsay; D'Souza, Rohan; Gates‐Ferris, Kathryn; Hurlbert, Marc; Anastario, Michael
Abstract This study compares rates of completion of client intake forms (CIFs) collected via three interview modes: audio computer‐assisted self‐interview (ACASI), face‐to‐face interview (FFI), and self‐administered paper‐based interview (SAPI). A total of 303 clients served through the Avon Breast Health Outreach Program (BHOP) were sampled from three U.S. sites. Clients were randomly assigned to complete a standard CIF via one of the three interview modes. Logistic regression analyses demonstrated that clients were significantly more likely to complete the entire CIF via ACASI than either FFI or SAPI. The greatest observed differences were between ACASI and SAPI; clients were almost six times more likely to complete the CIF via ACASI as opposed to SAPI (AOR = 5.8, p < .001). We recommend that where feasible, ACASI be utilized as an effective means of collecting client‐level data in healthcare settings. Adoption of ACASI in health centers may translate into higher completion rates of intake forms by clients, as well as reduced burden on clinic staff to enter data and review intake forms for completion.